Plasma volume variations in response to high intensity interval training in obese women: The influential role of menopausal status and age - Georges Jabbour; Maha Sellami; Horia-Daniel Iancu (Experimental Gerontology)
Objective: This study aims to explore the effects of high-intensity interval training (HIIT) on plasma volume (PV) variations in obese women, with a focus on understanding how menopausal status and age influence these changes. Methods: We enrolled fifty-nine obese women (perimenopausal and postmenopausal), aged approximately 56.6 years in a six-week HIIT program. Measurements of fitness, health, and PV were taken before and after the intervention. PV was assessed at two points during each session: at post-warm-up (PV1), and immediately post-training (PV2). These measurements were derived using hematocrit (Ht) and hemoglobin (Hb) values. Results: The intervention led to notable reductions in anthropometric measures and blood pressure (P < 0.01). For all women pre- and post-HIIT comparisons revealed significant differences in the extent of PV reduction at all two points (P < 0.01). Multiple linear regression analysis revealed that age was a significant contributor to the decreases in plasma volume (PV) observed both after warm-up and following the supramaximal cycling test - SCT (r = 0.44 and r = 0.57). On the other hand, menopause status was an independent predictor for PV decreases after warm-up (r = 0.33) as well after SCT (r = 0.38). Following HIIT, only menopause status accounted for 19 % of the variation in PV decreases after warm-up and 21 % of the variation in PV decreases after SCT. Conclusions: The findings suggest that HIIT is effective in enhancing plasma volume among obese menopausal women, attenuating the age-related decline in PV.